2019
DOI: 10.1186/s40425-018-0485-9
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor microenvironment modulation enhances immunologic benefit of chemoradiotherapy

Abstract: BackgroundChemoradiotherapy (CRT) remains one of the most common cancer treatment modalities, and recent data suggest that CRT is maximally effective when there is generation of an anti-tumoral immune response. However, CRT has also been shown to promote immunosuppressive mechanisms which must be blocked or reversed to maximize its immune stimulating effects.MethodsTherefore, using a preclinical model of human papillomavirus (HPV)-associated head and neck squamous cell carcinoma (HNSCC), we developed a clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 68 publications
1
63
0
Order By: Relevance
“…Various molecules, including IL-15, CD96, CD47, and CD137 have potential inhibitory effects. We also summarize receptor-mediated and combination therapeutic strategies for the activation of inflammatory pathways and immune cells [180]. On the other hand, radiotherapy can cause changes in gene expression in various cells in the tumor microenvironment.…”
Section: Combination Therapeutic Strategy For Combined Chemoradiotherapymentioning
confidence: 99%
“…Various molecules, including IL-15, CD96, CD47, and CD137 have potential inhibitory effects. We also summarize receptor-mediated and combination therapeutic strategies for the activation of inflammatory pathways and immune cells [180]. On the other hand, radiotherapy can cause changes in gene expression in various cells in the tumor microenvironment.…”
Section: Combination Therapeutic Strategy For Combined Chemoradiotherapymentioning
confidence: 99%
“…For many years, in order to improve the outcomes of RT, most studies focused on mechanisms internal to the cancer cell (intrinsic radiosensitivity), ignoring complex interactions between the tumor and the TME in which it grows (extrinsic radiosensitivity) [19][20][21]. Moreover, pre-clinical studies in some tumor models have suggested that RT-induced changes in the TME might, in fact, promote tumor invasion and spread the tumor in certain situations [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the effect of radiation on tumor cells could induce the release of new antigens and trigger the immune system to activate tumor-specific T cells. On the other hand, radiation could enhance TME immune infiltration, thereby overcoming some of the barriers to tumor rejection [19][20][21]. Cancer cells often express programmed cell death-ligand 1 (PD-L1) and subsequently induce T-cell apoptosis, and PD-L1 status is an important factor in the prediction of the clinical outcome following RT in BRCA patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…Mitigation of these two immunosuppressive cells using CTX and L-NIL (CTX/L-NIL) ultimately promoted enhanced infiltration of CD8 + T cells and improved survival in a mouse model of melanoma [31]. In an additional murine model of human papillomavirus (HPV) head and neck squamous cell carcinoma (HPV-HNSCC) we observed that CTX/L-NIL promotes even broader immunologic effects, including the upregulation of numerous anti-tumoral immune pathways such as antigen processing and presentation, myeloid trafficking and activation, and T cell function and co-stimulation [32]. We further found that its combination with chemoradiotherapy promoted favorable alterations in both the myeloid and lymphoid intratumoral microenvironment which significantly enhanced the therapeutic benefit of standard-of-care therapy [32].…”
Section: Introductionmentioning
confidence: 99%
“…In an additional murine model of human papillomavirus (HPV) head and neck squamous cell carcinoma (HPV-HNSCC) we observed that CTX/L-NIL promotes even broader immunologic effects, including the upregulation of numerous anti-tumoral immune pathways such as antigen processing and presentation, myeloid trafficking and activation, and T cell function and co-stimulation [32]. We further found that its combination with chemoradiotherapy promoted favorable alterations in both the myeloid and lymphoid intratumoral microenvironment which significantly enhanced the therapeutic benefit of standard-of-care therapy [32]. Thus, we hypothesized that CTX/L-NIL immunomodulation could promote a “cold to hot” transition of the TIME which could enhance treatment responses to ICI and radiation therapies.…”
Section: Introductionmentioning
confidence: 99%